2019
DOI: 10.1002/app.47405
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dielectric‐constant aromatic homopolyimide and copolyimide derived from pyromellitic dianhydride, 4,4′‐oxydianiline, 2,2‐bis[4‐(4‐aminephenoxy)phenyl]propane, 1,4‐bis(4‐aminophenoxy)benzene, or 1,3‐bis(4‐aminophenoxy)benzene

Abstract: Low‐dielectric‐constant aromatics, homopolyimide and copolyimide, were introduced. Homopolyimides were prepared by pyromellitic dianhydride (PMDA) as an anhydride monomer and 4,4′‐oxydianiline (ODA), 2,2‐bis[4‐(4‐aminephenoxy)phenyl]propane, 1,4‐bis(4‐aminophenoxy)benzene, or 1,3‐bis(4‐aminophenoxy)benzene as an amine monomer. The copolyimides were prepared with PMDA as an anhydride monomer, ODA as an amine monomer with the addition of 2,2‐bis[4‐(4‐aminephenoxy)phenyl]propane, 1,4‐bis(4‐aminophenoxy)benzene, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Up‐to‐now, polyimide (PI), polybenzoxazole (PBO), and benzocyclobutene (BCB) have been the most important insulating dielectric materials in the FO‐WLP 3–5 . And thereinto, PI has been widely employed as insulating layers and electronic packages in microelectronic industry due to their excellent thermal, mechanical, and dielectric properties 6–8 . However, with rapid development of the semiconductor industry, some critical properties such as low dielectric constant and low dissipation factor, 9,10 low coefficient thermal expansion (CTE), 11,12 high T g , 13,14 good mechanical strength, and superior hydrophobicity 15 become more and more important in the applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up‐to‐now, polyimide (PI), polybenzoxazole (PBO), and benzocyclobutene (BCB) have been the most important insulating dielectric materials in the FO‐WLP 3–5 . And thereinto, PI has been widely employed as insulating layers and electronic packages in microelectronic industry due to their excellent thermal, mechanical, and dielectric properties 6–8 . However, with rapid development of the semiconductor industry, some critical properties such as low dielectric constant and low dissipation factor, 9,10 low coefficient thermal expansion (CTE), 11,12 high T g , 13,14 good mechanical strength, and superior hydrophobicity 15 become more and more important in the applications.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] And thereinto, PI has been widely employed as insulating layers and electronic packages in microelectronic industry due to their excellent thermal, mechanical, and dielectric properties. [6][7][8] However, with rapid development of the semiconductor industry, some critical properties such as low dielectric constant and low dissipation factor, 9,10 low coefficient thermal expansion (CTE), 11,12 high T g , 13,14 good mechanical strength, and superior hydrophobicity 15 become more and more important in the applications. For example, one of critical challenge is to reduce the crosstalk and loss of signal at high frequency in the application of 5G communication in which the low dielectric constant and low dissipation factor materials are essential.…”
mentioning
confidence: 99%
“…This results in poor solubility and melt processability, which severely limit the application of aromatic polyimides. [15][16][17][18] To overcome these problems, different structural modifications were carried out to improve the solubility and processing characteristics of aromatic polyimides. It is well known that via adding a third monomer containing flexible segments, bulky groups and non-coplanar structures during copolymerization, these structures can be incorporated into the molecular chain of polyimides, thereby effectively improving their solubility and processability.…”
Section: Introductionmentioning
confidence: 99%
“…The rigidity of aromatic polyimides, such as Kapton (PMDA‐ODA type), Upliex‐s (s‐BPDA‐PDA type), arises from the stiff backbone structure, which leads to a strong interaction between the molecular chains. This results in poor solubility and melt processability, which severely limit the application of aromatic polyimides 15–18 …”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that incorporating trifluoromethyl groups into diamine moieties is a more effective design strategy to improve the transparency and coloration of semi-alicyclic PIs. Moreover, in terms of molecular design of intrinsic low dielectric PIs, increasing inherent free volume or incorporating groups with low electronic polarization was proved to be effective to reduce dielectric constant [ 30 , 31 , 32 ]. Bulky trifluoromethyl groups undoubtedly increased free volume in the molecular structures that can dilute the polar molecular concentration, and weaken electronic interaction between polymer chains [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%